TYPES OF AUTOIMMUNE POLYENDOCRINOPATIES IN CHILDREN WITH DIABETES MELLITUS TYPE 1 AND THYROID DISEASE - Gherbon Adriana (European Scientific Journal, ESJ, 2014)
Background&Aims: If are associated multiple autoimmuneendocrine diseases, the term is polyglandular autoimmune syndrome (PAS).The main autoimmune polyendocrinopaties encountered are: PAS I (chronicmucocutaneous candidiasis, chronic autoimmune hypoparathyroidism, andautoimmune Addison disease), PAS II (autoimmune Addison's disease,autoimmune thyroid disease and/or type 1 diabetes) and PAS III(autoimmune thyroid disease + other autoimmune diseases). The purpose ofthis study is to determine the types of PAS in a group of children withthyroid diseases and diabetes mellitus (DM) type 1.Methods: The studied group was of 83 children with DM type 1 (71 girlsand 12 boys), aged between 7 and 17 years. The methods of investigationwere represented by clinical, imaging, biochemical, hormonal andimmunological parameters.Results: The prevalence of PAS in the study group was: type I – 0%, type II- 6.02 % (80% girls and 20 % boys, p = 0.057, X2 = 3.6) and type III - 59.03% (85.71% girls and 14.29% boys, p < 0.001, X2 = 50). We don’t findsignificant differences between boys and girls in the case of PAS type II, butin type III prevailed girls, and the type was III a.Conclusions: The most frequent PAS was type III, subtype III a, follow bytype II. Because Addison's disease was asymptomatic, identifying throughthe presence of specified antibodies, if we have a children with two or moreautoimmune disease, we must investigate him for another possibleautoimmune disease.